Transcription Activator-Like Effector Nucleases (TALEN)-Mediated Targeted DNA Insertion in Potato Plants - Forsyth, Adrienne; Weeks, Troy; Richael, Craig; Duan, Hui (Frontiers in Plant Science, 2016)
Targeted DNA integration into known locations in the genome has potential advantages over the random insertional events typically achieved using conventional means of genetic modification. Specifically integrated transgenes are guaranteed to co-segregate, and expression level is more predictable, which makes downstream characterization and line selection more manageable. Because the site of DNA integration is known, the steps to deregulation of transgenic crops may be simplified. Here we describe a method that combines TALEN-mediated induction of double strand breaks (DSBs) and non-autonomous marker selection to insert a transgene into a pre-selected, transcriptionally active region in the potato genome. In our experiment, TALEN was designed to create a DSB in the genome sequence following an endogenous constitutive promoter. A cytokinin vector was utilized for TALENs expression and prevention of stable integration of the nucleases. The donor vector contained a gene of interest cassette and a promoter-less plant-derived herbicide resistant gene positioned near the T-DNA left border which was used to select desired transgenic events. Our results indicated that TALEN induced T-DNA integration occurred with high frequency and resulting events have consistent expression of the gene of interest. Interestingly, it was found that, in most lines integration took place through one sided homology directed repair despite the minimal homologous sequence at the right border. An efficient transient assay for TALEN activity verification is also described.